2023
DOI: 10.1371/journal.pone.0281125
|View full text |Cite
|
Sign up to set email alerts
|

Association of pro-inflammatory cytokines with trauma and post-traumatic stress disorder visiting a tertiary care hospital in Kathmandu

Abstract: Post-traumatic stress disorder (PTSD) is a mental disorder that can occur after trauma. Although inflammatory markers such as cytokines are found altered in trauma and PTSD, there is no consensus regarding which can be considered as biomarkers. Studies from South Asia region is also rare. We studied cytokines among trauma affected patients and matched healthy controls. Fifty patients (cases) with trauma, visiting the University hospital in Kathmandu and thirty-nine healthy controls were selected, and the level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 57 publications
2
4
0
Order By: Relevance
“… 27 This association between obesity and elevated F eno was no longer significant in healthy subpopulation 2, but the results suggest an associated trend ( Table IV ). Similar to our study, previous reports in nonasthmatic children 30 and adults 31 have reported a positive association between obesity and F eno . This may suggest that in healthy subjects without type 2 inflammation, unlike in people with asthma, obesity might increase F eno without mediating the mechanism of type 2 inflammation.…”
Section: Discussionsupporting
confidence: 93%
“… 27 This association between obesity and elevated F eno was no longer significant in healthy subpopulation 2, but the results suggest an associated trend ( Table IV ). Similar to our study, previous reports in nonasthmatic children 30 and adults 31 have reported a positive association between obesity and F eno . This may suggest that in healthy subjects without type 2 inflammation, unlike in people with asthma, obesity might increase F eno without mediating the mechanism of type 2 inflammation.…”
Section: Discussionsupporting
confidence: 93%
“…(Pillai et al 2016 ). Notably, a cross-sectional comparative study in Nepal identified strong association between pro-inflammatory cytokines and trauma, confirming the hypothesis of immune system activation in trauma (Koirala et al 2023 ). Similarly, Case-control studies in PTSD patients showed high levels of chemokines and proinflammatory cytokines, indicating that these increased inflammatory markers could act as biomarkers of PTSD risk, resilience, and stress responses (Zhang et al 2020 ; Otsuka et al 2021 ).…”
Section: Introductionsupporting
confidence: 67%
“…While specific cytokine changes, including the reduction in SFAS/FASLG, VEGF, CTACK/CCL27, IL9, IL6, MCP4, IL10, IL4, and increases in ENA78, GROA, IL2, TRACE, CCL21, FGF2, IL33, and TPO, did not achieve statistical significance individually, their collective alterations, as indicated by Z scores, may reveal a significant impact on the cytokine landscape in ME/CFS. Notably, IL4, IL6, IL9, IL10 ( 131 ), and IL33 play crucial roles in Th-2 immunity, the mast cell and eosinophil signaling network ( 132 138 ) ( Figure 7 ).…”
Section: Discussionmentioning
confidence: 99%